Stone Aggregations or Reefs? Knowledge Politics Around a Transboundary Seabed Complex - Irit Ittner; Anna‐Katharina Hornidge (Ocean and Society)
This study analyses marine governance and knowledge politics of sediments in the Borkum Reef Ground from a historical and German perspective, as well as in the context of litigation against marine gas production from transboundary Dutch and German fields. The authors analysed interview transcripts, project documents, environmental media campaigns, and notes originating from participant observation and stakeholder engagement. The study employs the science and technology and sociology of ignorance approaches. It asks which implications for biodiversity protection and ocean governance derive from administrative fragmentation and knowledge politics by a diverse set of actors. National divisions and prioritised knowledge production led to a shift in perception of the area from a transboundary seabed habitat to two distinct national marine areas and resulted in a fragmented Schutzgebietskulisse including marine protected areas, restoration zones, and unprotected zones. The study illustrates how the prioritisation of mapping marine protected areas may backfire on knowledge gain in potential industrial zones and overall marine protection.